1995
DOI: 10.1002/ajmg.1320550220
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of the urea cycle diseases: A survey of the european cases

Abstract: A European survey of prenatal diagnosis cases involving urea cycle diseases was performed. Citrullinemia was the most frequently investigated disease (108 cases). Other diseases are, in order of frequency, argininosuccinic aciduria (75 cases), ornithine transcarbamylase defect (52 cases), carbamoylphosphate synthetase defect (8 cases), triple H (3 cases), and arginase deficiency (1 case). Only one disease (ornithine transcarbamylase defect) is presently diagnosed using molecular biology methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…However, such an intervention is associated with a higher risk of complications, as compared with CVS or amniocentesis. In contrast to DNA-based prenatal diagnosis, enzymatic diagnosis of CPS1 deficiency by fetal liver biopsy may yield an ambiguous (Yoshino et al, 1997), or even misleading, result, as reported in one from eight diagnoses in a recent survey of European cases (Kamoun et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, such an intervention is associated with a higher risk of complications, as compared with CVS or amniocentesis. In contrast to DNA-based prenatal diagnosis, enzymatic diagnosis of CPS1 deficiency by fetal liver biopsy may yield an ambiguous (Yoshino et al, 1997), or even misleading, result, as reported in one from eight diagnoses in a recent survey of European cases (Kamoun et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These may also be indicated in milder UCDs or for NAGSD (which has substitutive therapy) for psychological reasons and to prepare for perinatal management [82-84]. Among the techniques that can be used (Table 3), mutation- or disease allele-tracking using chorionic villus samples, amniotic fluid cells or cultures thereof [85,86] is the method of choice since it gives rapid and clear-cut results relatively early on, with little fetal risk. Amniotic fluid citrulline and ASA determinations are also suitable for respective ASSD and ASLD prenatal diagnosis [86-88].…”
Section: Prenatal Testingmentioning
confidence: 99%
“…Elevated levels of argininosuccinic acid in the amniotic fluid can also reliably detect affected fetuses 40, 41, 42 . Analysis of enzyme activity by either direct methods from chorionic villus tissue or amniocytes or indirect methods such as 14 C-citrulline incorporation in uncultured chorionic villus samples, have been successfully performed 24, 43 .…”
Section: Diagnosismentioning
confidence: 99%